The Role of Youth in Enhancing Community Economic Welfare through the Development of Tourism Villages(A Study at the Pleseran Camp Earth Tourism in Nglurah Village, Tawangmangu, Karanganyar Regency) - Masda Marlena,, Elsa; Handoko, Trio; Choerudin, Achmad (Journal of Rural and Urban Community Studies, 2024)
Youth is part of a group of people who cannot be separated from all social problems. The youth of Nglurah Village, Tawangmangu District, have a very important and much-needed role in developing human resources in the community. So that the participation of the youth becomes a valuable resource for the progress of the village.The focus of this research is 1) What is the role of youth in improving the community's economy?, 2) How is the impact obtained by youth?, 3) What are the supporting and inhibiting factors for youth in developing Pleseran Camping Grounds?. 1) The aim of this research is to know the role of young youth in improving the community's economy. 2) Knowing the impact that the youth has with the existence of a tourist village. 3) Knowing what are the supporting and inhibiting factors for youth in developing the Ngelurah Tawangmangu Camping Ground Tourism Village The research approach used is a descriptive qualitative approach. Data collection techniques interview, observation and documentation. Source of data using primary data and secondary data. From the results of the study, it can be seen that village youth have increased the economy of BUPER tourist destinations by managing their participation, which has been carried out since the inception of the tourism village, in this case it can make youth a source of income. The impact obtained was very helpful and able to change economic conditions which were getting better. Supporting and inhibiting factors These supporting factors include: 1) Enthusiasm, 2) Unemployment Factor, 3) Community Factor, 4) Attraction of Nglurah Tawangmangu Tourism Village. And the inhibiting factors are: 1) The role of youth has not been fully utilized and 2) the lack of support from various parties